Peningkatan Minat Belajar Al-Qur'an Menggunakan Metode An-Nahdliyah - Ayu Meli Saputri; Arif Pambudi; Kurnia Dwi Putri (Yayasan Literasi Sains Indonesia, 2023)
In Baturaja Village there are people who are still weak in knowledge in the field of religious knowledge, especially in reading the Qur'an, because in Baturaja 3 Village there are still very few places to study the Qur'an and the majority of the people are busy with their own work. Non-formal educational institutions such as TPQ/TPA can be a means of learning to read the Koran. A good Al-Qur'an learning method will be able to simultaneously attract students' interest. TPQ Al Mubarok is located in a rural area where the community consists of various kinds. This study aims to increase interest or interest in learning the Qur'an, especially in reading the Qur'an properly and correctly. TPQ Al Mubarok itself is located in Baturaja 3 Village, Kec. North Sungkai Kab. North Lampung. This research uses classroom action research (CAR). The subjects of this study were class II students or those studying in volume II, with a total of 18 students consisting of 8 male students and 10 female students. Based on the results of testing in a research cycle about students' interest in learning in the learning process using the An-Nahdliyah method has increased.